Genetic Signatures From RNA Sequencing of Pediatric Localized Scleroderma Skin - Mirizio, Emily; Liu, Christopher; Yan, Qi; Waltermire, Julia; Mandel, Roosha; Schollaert, Kaila L.; Konnikova, Liza; Wang, Xinjun; Chen, Wei; Torok, Kathryn S. (Frontiers in Pediatrics, 2021)
The purpose of this study was to explore the skin transcriptional profile in pediatric localized scleroderma (LS) to provide a better understanding of the altered immune and fibrotic pathways promoting disease. LS is a progressive disease of the skin and underlying tissue that causes significant functional disability and disfigurement, especially in developing children. RNA sequencing (RNAseq) technology allows for improved understanding of relevant cellular expression through transcriptome analysis of phases during LS disease progression (more active/inflammatory vs. inactive/fibrotic) and also permits the use of RNA extracted from existing paraffin-embedded skin tissue, which is important in pediatrics. A strong correlation was observed between the comparison of genes expressed between fresh (RNAlater) and paraffinized skin in healthy and LS subjects, supporting the use of paraffinized tissue. LS gene signatures compared to healthy controls showed a distinct expression of an inflammatory response gene signature (IRGS) composed of IFNγ, IFNα and TNFα associated genes. GSEA© enrichment analysis showed the IRGS, including interferon inducible chemokines such as CXCL9, CXCL10, CXCL11 and IFNγ itself, was more highly expressed in LS patients with more inflammatory lesions. The use of paraffinized skin for sequencing was proven to be an effective substitute for fresh skin by comparing gene expression profiles. The prevalence of the IFNγ signature in the lesion biopsies of active LS patients indicates these genes reflect clinical activity parameters and may be the promoters of early, inflammatory disease.